Papillary renal cell carcinoma with cytologic and molecular genetic features overlapping with renal oncocytoma: Analysis of 10 cases - Michalova, Kvetoslava; Steiner, Petr; Alaghehbandan, Reza; Trpkov, Kiril; Martinek, Petr; Grossmann, Petr; Montiel, Delia Perez; Sperga, Maris; Straka, Lubomir; Prochazkova, Kristyna; Cempirkova, Dana; Horava, Vladimir; et al. (Annals of diagnostic pathology, 2018)
BACKGROUND: We present a series of papillary renal cell carcinomas (PRCC) reminiscent of so-called "oncocytic variant of papillary renal cell carcinoma" (OPRCC), included in the 2016 WHO classification as a potential type 3 PRCC. OPRCC is a poorly understood entity, cytologically characterized by oncocytic cells with non-overlapping low grade nuclei. OPRCC is not genotypically distinct and the studies concerning this variant have shown an inconsistent genetic profile. The tumors presented herein demonstrated predominantly papillary/tubulopapillary architecture and differed from OPRCC by pseudostratification and grade 2-3 nuclei (Fuhrman/ISUP). Because there is a morphologic overlap between renal oncocytoma (RO) and PRCC in the cases included in this study, the most frequently affected chromosomes in RO and PRCC were analyzed. MATERIALS AND METHODS: 147 PRCC composed of oncocytic cells were retrieved from our registry in order to select a group of morphologically uniform tumors. 10 cases with predominantly papillary, tubulopapillary or solid architectural patterns were identified. For immunohistochemical analysis, the following antibodies were used: vimentin, antimitochondrial antigene (MIA), AMACR, PAX8, CK7, CK20, AE1-3, CAM5.2, OSCAR, Cathepsin K, HMB45, SDHB, CD10, and CD117. Enumeration changes of locus 1p36, chromosomes 7, 14, 17, X, Y and rearrangement of CCND1 were examined by FISH. For further study, only tumors showing karyotype similar to that of RO were selected. The tumors exhibiting either trisomy of chromosomes 7, 17 or gain of Y, thus abnormalities characteristic for PRCC, were excluded. RESULTS: There were 5 males and 5 females, with patient age ranging from 56 to 79 years (mean 66.8 years). The tumor size ranged from 2 to 10 cm (mean 5.1 cm). Follow-up was available for 8/10 patients (mean 5.2 years); one patient died of the disease, while 7 of 8 are alive and well. Immunohistochemically, all cases were reactive for AMACR, vimentin, PAX8, OSCAR, CAM5.2, and MIA. SDHB was retained in all cases. 9/10 cases were positive for CD10, 7/10 cases reacted with CK7, 4/10 with Cathepsin K, and 2/10 with AE1-3. None of the cases were positive for CD117, HMB45 and CK20. All 10 cases were analyzable by FISH and showed chromosomal abnormalities similar to that usually seen in RO (i.e. loss of 1p36 gene loci, loss of chromosome Y, rearrangement of CCND1 and numerical changes of chromosome 14). CONCLUSIONS: We analyzed a series of renal tumors combining the features of PRCC/OPRCC and RO, that included pseudostratification and mostly high grade oncocytic cells lining papillary/tubulopapillary structures, karyotype characterized by loss of 1p36, loss of chromosome Y, rearrangement of CCND1 gene and numerical changes of chromosome 14. Despite the chromosomal numerical abnormalities typical of RO, we classified these tumors as part of the spectrum of PRCC because of their predominant papillary/tubulopapillary architecture, immunoprofile that included reactivity for AMACR, vimentin and lack of reactivity for CD117, all of which is incompatible with the diagnosis of RO. This study expands the morphological spectrum of PRCC by adding a cohort of diagnostically challenging cases, which may be potentially aggressive.
Keywords: Carcinoma, Papillary; diferenciální diagnóza; Female; ženské pohlaví; Adenoma, Oxyphilic; oxyfilní adenom; lidé; karcinom z renálních buněk; Diagnosis, Differential; Kidney Neoplasms; Carcinoma, Renal Cell; papilární karcinom; Male; nádorové biomarkery; chromozomální aberace; Aged; nádory ledvin; Biomarkers, Tumor; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Chromosome Aberrations; Humans